Nonaqueous electrolyte storage element and method for producing the same

By incorporating a specific compound that undergoes polymerization on the positive electrode active material surface, the nonaqueous electrolyte storage device achieves high capacity retention and low resistance increase after charge/discharge cycles, addressing the challenges faced by conventional devices.

JP7665932B2Active Publication Date: 2025-04-22GS YUASA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020137629
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-17
Publication Date
2025-04-22
Estimated Expiration
2040-08-17

AI Technical Summary

Technical Problem

Nonaqueous electrolyte storage devices, such as lithium-ion batteries, experience a decrease in discharge capacity over charge and discharge cycles due to cracking of positive electrode active material particles and the formation of resistive surface layers.

Method used

Incorporating a compound represented by the formula R1-R2-R3-n, where R1, R2, and R3 can be hydrogen, halogen, hydrocarbon, or alkoxy groups, and n is an integer between 1 and 4, into the nonaqueous electrolyte. This compound undergoes polymerization on the positive electrode active material surface during charging, forming a conductive polymer that maintains the electron conduction path and reduces surface resistance.

Benefits of technology

The use of this compound in the nonaqueous electrolyte storage device results in a high capacity retention rate and a low resistance increase rate after charge/discharge cycles, effectively addressing the issues of capacity loss and resistance increase in conventional devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665932000018
    Figure 0007665932000018
  • Figure 0007665932000019
    Figure 0007665932000019
  • Figure 0007665932000001
    Figure 0007665932000001
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte power storage element having a high capacity retention rate after a charge / discharge cycle, and a manufacturing method of the non-aqueous electrolyte power storage element.SOLUTION: A non-aqueous electrolyte power storage element including a positive electrode containing a positive electrode active material and a non-aqueous electrolyte containing a compound represented by the following formula 1. (In the formula 1, R1, R2, and a plurality of R3 are independently hydrogen atom, halogen atom, hydrocarbon group having 1 or more and 20 or less carbon atoms, halogenated hydrocarbon group having 1 or more and 20 or less carbon atoms, an alkoxy group having 1 or more and 20 or less carbon atoms, or a halogenated alkoxy group having 1 or more and 20 or less carbon atoms. n is an integer between 1 and 4 ).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonaqueous electrolyte electricity storage element and a method for producing a nonaqueous electrolyte electricity storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries.

[0003] In addition to a nonaqueous solvent and an electrolyte salt, the nonaqueous electrolyte of a nonaqueous electrolyte storage element may contain various additives for the purpose of improving performance, etc. For example, Patent Document 1 proposes a nonaqueous electrolyte secondary battery provided with a nonaqueous electrolyte solution containing biphenyl and / or a biphenyl derivative. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-69659 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is desirable for a non-aqueous electrolyte storage element to maintain its initial good performance even after repeated charge and discharge, but the discharge capacity of a non-aqueous electrolyte storage element usually decreases gradually with increasing charge and discharge cycles.

[0006] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a nonaqueous electrolyte storage element having a high capacity retention rate after charge-discharge cycles, and a method for manufacturing such a nonaqueous electrolyte storage element. [Means for solving the problem]

[0007] A nonaqueous electrolyte electricity storage element according to one embodiment of the present invention is a nonaqueous electrolyte electricity storage element including a positive electrode containing a positive electrode active material, and a nonaqueous electrolyte containing a compound represented by the following formula 1. [ka] (In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 20 carbon atoms, a halogenated hydrocarbon group having from 1 to 20 carbon atoms, an alkoxy group having from 1 to 20 carbon atoms, or a halogenated alkoxy group having from 1 to 20 carbon atoms. n is an integer of from 1 to 4.

[0008] A method for producing a nonaqueous electrolyte storage element according to another embodiment of the present invention includes preparing a positive electrode containing a positive electrode active material, and preparing a nonaqueous electrolyte containing a compound represented by the following formula 1: [ka] (In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 20 carbon atoms, a halogenated hydrocarbon group having from 1 to 20 carbon atoms, an alkoxy group having from 1 to 20 carbon atoms, or a halogenated alkoxy group having from 1 to 20 carbon atoms. n is an integer of from 1 to 4. Effect of the Invention

[0009] The nonaqueous electrolyte electricity storage element according to one embodiment of the present invention has a high capacity retention rate after charge-discharge cycles. According to a method for producing a nonaqueous electrolyte electricity storage element according to another aspect of the present invention, a nonaqueous electrolyte electricity storage element having a high capacity retention rate after charge / discharge cycles can be produced. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is an external perspective view showing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] First, an outline of the nonaqueous electrolyte storage element and the method for producing the nonaqueous electrolyte storage element disclosed in this specification will be described.

[0012] A nonaqueous electrolyte electricity storage element according to one embodiment of the present invention is a nonaqueous electrolyte electricity storage element including a positive electrode containing a positive electrode active material, and a nonaqueous electrolyte containing a compound represented by the following formula 1. [ka] (In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 20 carbon atoms, a halogenated hydrocarbon group having from 1 to 20 carbon atoms, an alkoxy group having from 1 to 20 carbon atoms, or a halogenated alkoxy group having from 1 to 20 carbon atoms. n is an integer of from 1 to 4.

[0013] The nonaqueous electrolyte storage element has a high capacity retention rate after charge-discharge cycles. The reason why the above effect occurs in the nonaqueous electrolyte storage element is unclear, but the following reasons are presumed. In a conventional nonaqueous electrolyte storage element, the discharge capacity decreases with charge-discharge cycles due to cracking caused by expansion and contraction of the positive electrode active material particles, which breaks the electron conduction path between the positive electrode active material particles, which reduces the conductivity of the positive electrode, and due to the outflow of components in the positive electrode active material particles into the nonaqueous electrolyte, which forms a highly resistant surface layer on the surface of the positive electrode active material particles. In contrast, in the nonaqueous electrolyte storage element, the compound represented by the above formula 1 contained in the nonaqueous electrolyte is oxidized on the surface of the positive electrode active material particles during charging, causing a polymerization reaction, and it is believed that the compound becomes a conductive polymer and adheres to the surface of the positive electrode active material particles. If such a conductive polymer adheres to the part where the electron conduction path between the positive electrode active material particles is broken, the electron conduction path is maintained, and the decrease in the conductivity of the positive electrode is suppressed. In addition, even if defects such as cracking of the positive electrode active material particles or outflow of components do not occur, the conductive polymer adheres to the surface of the positive electrode active material particles or between the positive electrode active material particles, thereby increasing the conductivity of the positive electrode or suppressing the decrease in conductivity. For this reason, it is presumed that the nonaqueous electrolyte storage element can suppress the decrease in discharge capacity accompanying the charge / discharge cycle, and the capacity retention rate after the charge / discharge cycle is increased. In addition, as shown in the comparative example described later, when biphenyl, which is thought to become a conductive polymer when polymerized in the same manner, is used, the above effect is low. This is presumed to be due to the fact that the benzene ring of biphenyl undergoes a polymerization reaction at a higher potential than the thiophene ring of the compound represented by the above formula 1, and is difficult to adhere to the surface of the positive electrode active material. In addition, since the compound represented by the above formula 1 contains sulfur atoms, it is presumed that the conductive polymer containing sulfur formed on the surface of the positive electrode active material particles acts as a sacrificial oxidant, and in particular, when a lithium transition metal composite oxide is contained as the positive electrode active material, it is reduced the release of oxygen from the lithium transition metal composite oxide, and the deterioration associated with the alteration of the surface of the positive electrode active material is suppressed.

[0014] In addition, the nonaqueous electrolyte storage element has an advantage that the resistance increase rate after charge / discharge cycles is low. The reason for this is also unclear, but it is presumed that the conductive polymer containing sulfur formed by the compound represented by formula 1 above improves the conductivity of the positive electrode, or that the deterioration associated with the alteration of the surface of the positive electrode active material is suppressed.

[0015] The above n is preferably 2. In such a case, the capacity retention rate after charge / discharge cycles can be further increased and the resistance increase rate can be further decreased.

[0016] Above R 1 , R 2 and multiple R 3 are each preferably independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 3 carbon atoms, a halogenated hydrocarbon group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, or a halogenated alkoxy group having 1 to 3 carbon atoms. In such a case, the capacity retention rate after charge / discharge cycles can be increased and the resistance increase rate can be reduced. The reason for this is unclear, but it is presumed that because these substituents are groups with a relatively small number of carbon atoms, steric hindrance is unlikely to occur and the polymerization reaction proceeds easily.

[0017] Above R 1 and R 2 are preferably hydrogen atoms. In such a case, the capacity retention rate after charge / discharge cycles can be increased and the resistance increase rate can be reduced. Although the reason for this is unclear, it is speculated that the compound represented by the above formula 1 has at least a part of unsubstituted thiophene rings at both ends of the molecule, which facilitates the polymerization reaction and makes it easier to form a long-chain conductive polymer.

[0018] The positive electrode active material may contain a lithium transition metal composite oxide containing nickel, and the content ratio of nickel in the transition metal in the lithium transition metal composite oxide may be 50 mol % or more. A lithium transition metal composite oxide having a high content ratio of nickel is a positive electrode active material that is prone to cracking due to repeated charging and discharging. Therefore, when the nonaqueous electrolyte storage element contains such a lithium transition metal composite oxide as a positive electrode active material, the advantage of suppressing the decrease in discharge capacity due to charge and discharge cycles caused by cracking of the positive electrode active material and increasing the capacity maintenance rate after charge and discharge cycles is more effectively obtained. In addition, a conventional nonaqueous electrolyte storage element containing such a lithium transition metal composite oxide having a high content ratio of nickel as a positive electrode active material significantly increases the resistance due to charge and discharge cycles caused by cracking of the positive electrode active material. In addition, when the content ratio of nickel is high, oxygen is easily released from the lithium transition metal composite oxide. Therefore, when the nonaqueous electrolyte storage element contains such a lithium transition metal composite oxide as a positive electrode active material, the advantage of reducing the resistance increase rate after charge and discharge cycles is particularly sufficiently obtained.

[0019] The positive electrode active material may be a secondary particle. The positive electrode active material of secondary particles is also a positive electrode active material that is prone to cracking due to repeated charging and discharging, such as gaps being easily generated between primary particles. Therefore, when the nonaqueous electrolyte storage element includes such a positive electrode active material of secondary particles, the advantages of suppressing the decrease in discharge capacity and the increase in resistance due to the charge-discharge cycle caused by the cracking of the positive electrode active material, increasing the capacity retention rate after the charge-discharge cycle, and reducing the resistance increase rate can be more effectively obtained. In addition, when such a positive electrode active material of secondary particles is used, the surface area of ​​the positive electrode active material is large, so that the output performance can be improved.

[0020] A method for producing a nonaqueous electrolyte storage element according to another embodiment of the present invention includes preparing a positive electrode containing a positive electrode active material, and preparing a nonaqueous electrolyte containing a compound represented by the following formula 1: [ka] (In formula 1, R1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 20 carbon atoms, a halogenated hydrocarbon group having from 1 to 20 carbon atoms, an alkoxy group having from 1 to 20 carbon atoms, or a halogenated alkoxy group having from 1 to 20 carbon atoms. n is an integer of from 1 to 4.

[0021] According to this manufacturing method, a nonaqueous electrolyte electricity storage element having a high capacity retention rate after charge-discharge cycles can be manufactured. In addition, the nonaqueous electrolyte electricity storage element manufactured by this manufacturing method has the advantage of having a low resistance increase rate after charge-discharge cycles.

[0022] A nonaqueous electrolyte storage element according to an embodiment of the present invention, a method for manufacturing a nonaqueous electrolyte storage element, and other embodiments will be described in detail below. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.

[0023] <Non-aqueous electrolyte electricity storage element> The nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode, and a nonaqueous electrolyte. The nonaqueous electrolyte storage element may further have a separator. Hereinafter, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as a "secondary battery") will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are usually stacked or wound alternately through a separator to form an electrode body. That is, the electrode body is usually composed of a positive electrode, a negative electrode, and a separator. This electrode body is stored in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the container, a known metal container, a resin container, etc. that are usually used as a container for a secondary battery can be used.

[0024] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0025] The positive electrode substrate has electrical conductivity. Here, the term "electrically conductive" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Having no electrical conductivity" means that the volume resistivity is 10 7 It means that the electrical resistance is more than Ω·cm. Metals such as aluminum, titanium, tantalum, stainless steel, etc., or alloys thereof are used as the material of the substrate. Among these, aluminum and aluminum alloys are preferred from the viewpoint of the balance between high electrical conductivity and cost. The form of the positive electrode substrate can be foil, evaporated film, etc., and foil is preferred from the viewpoint of cost. In other words, aluminum foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085P and A3003P, etc., as specified in JIS-H-4000 (2014).

[0026] The average thickness of the positive electrode substrate is preferably 3 μm or more and 100 μm or less, more preferably 5 μm or more and 60 μm or less, even more preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate while increasing the energy density per volume of the secondary battery. The "average thickness" refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate. The "average thickness" is also defined in the same way when used for other members, etc.

[0027] The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains conductive particles (conductive particles) such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.

[0028] The positive electrode active material layer is a layer formed from a positive electrode mixture. The positive electrode mixture (positive electrode active material layer) contains a positive electrode active material. The positive electrode mixture (positive electrode active material layer) contains optional components such as a conductive agent, a binder, a thickener, a filler, and a dispersant as necessary.

[0029] The positive electrode active material may be a lithium transition metal composite oxide or a polyanion compound. The lithium transition metal composite oxide may be, for example, Li x MeO y (Me represents at least one transition metal) x CoO2, Li x NiO2, Li x MnO3, Li x Ni α Co 1-α O2, Li x Ni α Co β Al 1-α-β O2, Li x Ni α Mn β Co 1-α-β O2, Li 1+x (Ni α Mn β Co 1-α-β ) 1-x Li with spinel crystal structure such as O2 x Mn2O4, Li x Ni α Mn 2-α O4, etc. Also, examples of polyanion compounds include Li w Me x (XO y ) z (Me represents at least one kind of transition metal, and X represents, for example, P, Si, B, V, etc.) polyanion compounds (LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc.) may be mentioned. The elements or polyanions in these compounds may be partially substituted with other elements or anion species. The surfaces of these compounds may be coated with other materials. In the positive electrode active material layer, one of these compounds may be used alone, or two or more of them may be used in combination.

[0030] The positive electrode active material may contain a lithium transition metal composite oxide containing nickel. The lower limit of the content ratio (Ni / Me) of nickel (Ni) in the transition metal (Me) in the lithium transition metal composite oxide containing nickel may be, for example, 30 mol%, but is preferably 50 mol%. By using such a lithium transition metal composite oxide with a high content ratio of nickel, the electric capacity can be increased. On the other hand, the upper limit of the content ratio of nickel (Ni / Me) may be, for example, 100 mol% or 90 mol%. The content ratio of nickel (Ni / Me) may be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0031] The lithium transition metal composite oxide containing nickel preferably further contains at least one of manganese and cobalt, and more preferably further contains both manganese and cobalt. The content ratio (Mn / Me) of manganese (Mn) in the transition metal (Me) in the lithium transition metal composite oxide containing nickel is preferably 5 mol% to 50 mol%, and more preferably 10 mol% to 40 mol%. The content ratio (Co / Me) of cobalt (Co) in the transition metal (Me) in the lithium transition metal composite oxide containing nickel is preferably 5 mol% to 50 mol%, and more preferably 10 mol% to 40 mol%.

[0032] The content ratio (Li / Me) of lithium (Li) to transition metal (Me) in the nickel-containing lithium transition metal composite oxide is preferably 1 or more and 1.5 or less in molar ratio, and may be 1.

[0033] As the lithium transition metal composite oxide containing nickel, one containing aluminum is also preferred.

[0034] As an example of a lithium transition metal composite oxide containing nickel, there is LiFeO2 having a layered α-NaFeO2 type crystal structure. x NiO2(1≦x≦1.5), Li x Ni α Co 1-αO2 (1 ≤ x ≤ 1.5, 0.5 ≤ α < 1), Li x Ni α Co β Al 1-α-β O2 (1 ≤ x ≤ 1.5, 0.5 ≤ α < 1, 0 < β ≤ 0.5), Li x Ni α Mn β Co 1-α-β O2 (1 ≤ x ≤ 1.5, 0.5 ≤ α < 1, 0 < β ≤ 0.5), Li 1+x (Ni α Mn β Co 1-α-β ) 1-x O2 (0 < x < 1, 0.5 ≤ α < 1, 0 < β ≤ 0.5), etc.; Li having a spinel crystal structure x Ni α Mn 2-α O4 (1 ≤ x ≤ 1.5, 1 ≤ α ≤ 2), etc. can be mentioned.

[0035] Specific examples of lithium transition metal composite oxides containing nickel include, for example, LiNi 3 / 5 Co 1 / 5 Mn 1 / 5 O2, LiNi 1 / 2 Co 1 / 5 Mn 3 / 10 O2, LiNi 1 / 2 Co 3 / 10 Mn 1 / 5 O2, LiNi 8 / 10 Co 1 / 10 Mn 1 / 10 O2, etc. can be mentioned. Note that the composition of the positive electrode active material indicates the composition in the state before the first charging process (i.e., the charging process performed for the first time after assembling battery components such as the positive electrode, negative electrode, and non-aqueous electrolyte).

[0036] Lithium transition metal composite oxides with a high nickel content have a large capacitance, but are prone to cracking with repeated charge and discharge. Therefore, when a lithium transition metal composite oxide with a high nickel content is used as a positive electrode active material, the advantages of the secondary battery, such as suppressing the decrease in discharge capacity and the increase in resistance associated with the charge and discharge cycle due to the interruption of the electron conduction path between the positive electrode active material particles, increasing the capacity retention rate after the charge and discharge cycle, and reducing the resistance increase rate, can be more effectively achieved.

[0037] Similarly, when using a positive electrode active material that is prone to forming a high-resistance surface layer on the surface of the positive electrode active material particles due to the outflow of components (such as iron and manganese) in the positive electrode active material into the non-aqueous electrolyte with repeated charge and discharge, the advantages of the secondary battery can be more effectively achieved. Examples of positive electrode active materials from which iron or manganese can flow out into the non-aqueous electrolyte due to repeated charge and discharge include, for example, iron phosphate-based positive electrode active materials (such as LiFePO4), manganese phosphate-based positive electrode active materials (such as LiMnPO4), lithium manganate-based positive electrode active materials (such as LiMn2O4), and lithium-excess type lithium transition metal composite oxides containing manganese (Li 1+x (Mn α Me 1-α ) 1-x O2 (Me is a transition metal other than manganese, 0 < x < 1, 0.4 ≦ α < 1), etc.). Elements or polyanions in these compounds may be partially substituted with other elements or anion species.

[0038] The content of the lithium transition metal composite oxide containing nickel or the positive electrode active material in which iron or manganese may flow out to the non-aqueous electrolyte by charging and discharging in the total positive electrode active material is preferably 70% by mass or more and 100% by mass or less, more preferably 90% by mass or more, and even more preferably 95% by mass or more. By setting the content of these specific positive electrode active materials in the above range, it is possible to achieve both high energy density and manufacturability of the positive electrode active material layer. In addition, in the case of a conventional positive electrode, when the content ratio of these specific positive electrode active materials in the total positive electrode active material is high, the conductivity tends to be easily reduced due to cracking or outflow of components. Therefore, in one embodiment of the present invention, when the content of these positive electrode active materials in the total positive electrode active material is equal to or more than the above lower limit, the advantages of the secondary battery are more effectively exhibited.

[0039] The positive electrode active material is usually a particle (powder). The positive electrode active material is preferably a secondary particle. By being a secondary particle, the surface area is increased, and output performance, etc. can be improved. On the other hand, in the case of secondary particles, cracks are likely to occur with repeated charging and discharging. Therefore, when the positive electrode active material is a secondary particle, the decrease in discharge capacity and the increase in resistance due to the charge-discharge cycle caused by the interruption of the electron conduction path between the positive electrode active material particles can be suppressed, and the advantages of the secondary battery, such as increasing the capacity retention rate and decreasing the resistance increase rate after the charge-discharge cycle, can be more effectively achieved.

[0040] The primary particle diameter (average particle diameter) of the positive electrode active material is preferably 300 nm or more and 1 μm or less. The secondary particle diameter (average particle diameter) of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the primary particle diameter and secondary particle diameter of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting each average particle diameter to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. When a composite of the positive electrode active material and another material is used, the average particle diameter of the composite is taken as the secondary particle diameter of the positive electrode active material. The "average particle diameter" of the secondary particles is determined by the following method. Based on the particle diameter distribution measured by the laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013), the value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% is taken as the average particle diameter of the secondary particles. The "average particle diameter" of the primary particles is determined by the following method. At least 50 primary particles constituting the positive electrode active material particles are observed on the surface of the positive electrode active material layer observed by a scanning electron microscope (SEM), and the length of the major axis of each particle is calculated by image analysis, and the average value is taken as the average particle size of the primary particles. The observation conditions of the SEM are not particularly limited, but the magnification is usually 10,000 to 100,000 times (for example, 50,000 times).

[0041] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.

[0042] The content of the positive electrode active material in the positive electrode active material layer can be, for example, from 80% by mass to 98% by mass, and is preferably 90% by mass or more.

[0043] The conductive agent is not particularly limited as long as it is a material having conductivity that does not adversely affect the performance of the secondary battery. Examples of such conductive agents include natural or artificial graphite, carbon black such as furnace black, acetylene black, and ketjen black, metals, conductive ceramics, etc., and acetylene black is preferred. The conductive agent may be in the form of powder, fiber, etc.

[0044] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.

[0045] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like.

[0046] The filler is not particularly limited as long as it does not adversely affect the performance of the secondary battery. Examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, and glass.

[0047] The positive electrode active material layer (positive electrode mixture) may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0048] At the positive electrode, the potential is 3.00 V vs. Li / Li + From the discharge state, the potential is 4.35V vs. Li / Li +The increase rate of the BET specific surface area of ​​the positive electrode active material layer when the positive electrode active material layer is in a charged state may be 15% or more, 30% or more, or 45% or more. In the case of a positive electrode active material layer having a large increase rate of the BET specific surface area when the positive electrode active material layer is in a charged state from a discharged state, the positive electrode active material particles are likely to crack. Therefore, in the case of such a positive electrode active material layer, the effect of the secondary battery is more fully exhibited. On the other hand, the increase rate of the BET specific surface area may be, for example, 100% or less, or 70% or less.

[0049] The increase rate of the BET specific surface area is determined by the following method. The surface area of ​​the positive electrode is measured by a nitrogen gas adsorption method using a multipoint method in a relative pressure range of 0.05 to 0.2. The obtained surface area (adsorbed amount of nitrogen gas: m 2 ) by the mass (g) of the positive electrode active material layer to obtain the BET specific surface area (m 2 / g) is obtained. The BET specific surface area of ​​the positive electrode active material layer is obtained for each of the positive electrodes in the discharged and charged states, and the increase rate is calculated. Since the increase rate of the BET specific surface area is measured, it can be measured in the same manner even in the case of a positive electrode having a portion where the positive electrode active material layer is not laminated. In other words, the "increase rate of the BET specific surface area of ​​the positive electrode active material layer" may be the "increase rate of the BET specific surface area of ​​the positive electrode." In addition, when the potential is 3.00 V vs. Li / Li + The discharged positive electrode and potential are 4.35V vs. Li / Li + The positive electrode in the charged state has a potential adjusted by the following method. Potential is 3.00V vs. Li / Li + The discharged positive electrode is 3.00V vs. Li / Li at 25℃. + Discharge at a constant current of 0.2C until the battery reached 3.00V vs. Li / Li after a 10-minute rest period. + This is obtained by performing a constant current discharge at a discharge current of 0.05C up to 4.35V vs. Li / Li + The positive electrode in the charged state is 4.35V vs. Li / Li at 25℃. +After charging at a constant current of 0.2C, the total charging time was 7 hours, and the battery voltage was 4.35V vs. Li / Li + In this case, a half cell with a Li counter electrode or a full cell with a Li reference electrode inserted may be used.

[0050] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer, which may have the same structure as the intermediate layer of the positive electrode.

[0051] The negative electrode substrate can have the same structure as the positive electrode substrate, but the material is a metal such as copper, nickel, stainless steel, nickel-plated steel, or an alloy thereof, and copper or a copper alloy is preferred. That is, the negative electrode substrate is preferably a copper foil. Examples of the copper foil include rolled copper foil and electrolytic copper foil.

[0052] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.

[0053] The negative electrode active material layer is formed from a negative electrode mixture containing a negative electrode active material. This negative electrode mixture (negative electrode active material layer) contains optional components such as a conductive agent, a binder, a thickener, a filler, a dispersant, etc. as necessary. The optional components such as the conductive agent, the binder, the thickener, the filler, the dispersant, etc. may be the same as those in the positive electrode active material layer.

[0054] The negative electrode active material layer (negative electrode mixture) may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0055] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 Examples of the material include titanium-containing oxides such as LiTiO2 and TiNb2O7; polyphosphate compounds; silicon carbide; and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0056] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0057] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0058] Here, the "discharged state" refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode. Since the potential of the metallic Li counter electrode in the open circuit state is approximately equal to the redox potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the redox potential of Li. In other words, the open circuit voltage of 0.7 V or more in the single-electrode battery means that lithium ions capable of being absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.

[0059] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0060] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0061] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 μnm or more and 100 μm or less. When the negative electrode active material is, for example, a carbon material, the average particle size may be preferably 1 μm or more and 100 μm or less. When the negative electrode active material is a metal, a semi-metal, a metal oxide, a semi-metal oxide, a titanium-containing oxide, a polyphosphate compound, or the like, the average particle size may be preferably 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the production or handling of the negative electrode active material becomes easy. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverization method and the powder classification method can be selected, for example, from the methods exemplified for the positive electrode.

[0062] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0063] (Non-aqueous electrolyte) The non-aqueous electrolyte contains a compound represented by the following formula 1. The non-aqueous electrolyte may be a non-aqueous electrolytic solution. In addition to the above compound, the non-aqueous electrolyte usually contains a non-aqueous solvent and an electrolyte salt.

[0064] It is assumed that the above compound undergoes a polymerization reaction on the surface of the positive electrode active material particles upon charging, and becomes a conductive polymer that adheres to the surface of the positive electrode active material particles. However, the volume resistivity of the conductive polymer that is assumed to adhere to the surface of the positive electrode active material particles in this way is not particularly limited, and the volume resistivity is preferably 10 7 It may be more than Ω·cm.

[0065] [ka]

[0066] In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 20 carbon atoms, a halogenated hydrocarbon group having from 1 to 20 carbon atoms, an alkoxy group having from 1 to 20 carbon atoms, or a halogenated alkoxy group having from 1 to 20 carbon atoms. n is an integer of 1 to 4.

[0067] Examples of the halogen atom include a chlorine atom and a fluorine atom.

[0068] Examples of the hydrocarbon group include Alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, and decyl groups; alkenyl groups such as ethenyl, propenyl, and butenyl; aliphatic chain hydrocarbon groups such as alkynyl groups, e.g., ethynyl, propynyl, butynyl, etc.; cycloalkyl groups such as cyclohexyl groups; Monovalent alicyclic hydrocarbon groups such as cycloalkenyl groups, e.g., cyclohexenyl groups; and Aromatic hydrocarbon groups such as phenyl, naphthyl, biphenyl, and benzyl groups Examples include:

[0069] Examples of the halogenated hydrocarbon group include the above-mentioned hydrocarbon groups in which some or all of the hydrogen atoms have been substituted with halogen atoms.

[0070] The alkoxy group refers to a group in which an oxygen atom is bonded to a hydrocarbon group (-OR: R is a hydrocarbon group). Examples of the alkoxy group include the groups in which an oxygen atom is bonded to each of the above-mentioned hydrocarbon groups.

[0071] Examples of the halogenated alkoxy group include the above-mentioned alkoxy groups in which some or all of the hydrogen atoms have been substituted with halogen atoms.

[0072] R 1 , R 2 and multiple R 3 Each of the groups preferably has 12 or less carbon atoms, and more preferably has 6 or less carbon atoms. For example, the group having 12 or less carbon atoms includes a group (atom) that does not contain carbon, that is, a group having 0 carbon atoms (hydrogen atom and halogen atom). Thus, the substituent R 1 , R 2 and R 3 When is a group having a relatively small number of carbon atoms, steric hindrance is small and a conductive polymer is easily formed, so that the capacity retention rate after charge / discharge cycles can be increased and the resistance increase rate can be reduced.

[0073] R 1 and R 2 More preferably, R is independently a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 3 carbon atoms, a halogenated hydrocarbon group having from 1 to 3 carbon atoms, an alkoxy group having from 1 to 3 carbon atoms, or a halogenated alkoxy group having from 1 to 3 carbon atoms. 1 and R 2 It is more preferable that each of R is independently a hydrogen atom or a hydrocarbon group. 1 and R2 is more preferably each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, and even more preferably a hydrogen atom.

[0074] Multiple R 3 are each independently preferably a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 3 carbon atoms, a halogenated hydrocarbon group having from 1 to 3 carbon atoms, an alkoxy group having from 1 to 3 carbon atoms, or a halogenated alkoxy group having from 1 to 3 carbon atoms. 3 It is more preferable that each R is independently a hydrogen atom or a hydrocarbon group. 3 More preferably, each independently represents a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms. 3 In some cases, it may be more preferred that at least one of the groups is a hydrocarbon group.

[0075] Also, R 1 , R 2 and multiple R 3 It is preferable that two or more of R are hydrogen atoms. 1 and R 2 It is more preferable that both of are hydrogen atoms. In this way, the compound represented by the above formula 1 has at least two groups having unsubstituted thiophene rings, and preferably has at least a portion (preferably the 5-position) of an unsubstituted thiophene ring at both ends of the molecule, which facilitates the polymerization reaction to proceed, thereby making it possible to further increase the capacity retention rate and reduce the resistance increase rate after charge / discharge cycles.

[0076] n is preferably 2 or more. By using a compound having a dimer or more as the compound represented by the above formula 1, a polymer having a high degree of polymerization is easily formed, and as a result, the capacity retention rate after charge / discharge cycles can be increased and the resistance increase rate can be reduced. On the other hand, n is preferably 3 or less, and more preferably 2 or less. By making the value of n relatively small, the solubility in non-aqueous solvents is increased, and a sufficient amount of the compound represented by the above formula 1 can be dissolved in the non-aqueous solvent. For this reason, n is particularly preferably 2.

[0077] A preferred embodiment of the compound represented by the above formula 1 is a compound represented by the following formula 2.

[0078] [ka]

[0079] In formula 2, R 1 and R 2 is R in Eq. 1 and R 2 Synonymous with R. 3a , R 3b , R 3c and R 3d each independently represents R in formula 1 3 m is an integer of 0 to 3. When m is 2 or more, multiple R 3c and multiple R 3d may be the same or different.

[0080] R in Equation 2 1 and R 2 Specific and preferred embodiments of the formula are R 1 and R 2 is the same as:

[0081] R in Equation 2 3a , R 3b , R 3c and R 3d Specific and preferred embodiments of the formula are R 3 Same as R 3aand R 3d R may preferably be a hydrogen atom. 3b and R 3c In some cases, a hydrocarbon group having 1 to 6 carbon atoms is preferred, and in other cases, a hydrocarbon group having 1 to 3 carbon atoms is more preferred.

[0082] m is preferably 0 or more and 2 or less, and in some cases 1 or less or 1 or more is preferable, with 1 being particularly preferable.

[0083] The content of the compound represented by the above formula 1 in the non-aqueous electrolyte is not particularly limited, but is preferably 0.005% by mass or more and 5% by mass or less, more preferably 0.01% by mass or more and 1% by mass or less, even more preferably 0.02% by mass or more and 0.2% by mass or less, even more preferably 0.03% by mass or more and 0.1% by mass or less, and even more preferably 0.04% by mass or more and 0.08% by mass or less. The above content may be more preferably 0.06% by mass or more or 0.08% by mass or more. By setting the content of the compound represented by the above formula 1 to the above lower limit or more, a sufficient amount of conductive polymer is formed, and the capacity retention rate after charge / discharge cycles can be increased and the resistance increase rate can be reduced. On the other hand, by setting the content to the above upper limit or less, the side reaction of the compound represented by the above formula 1 is suppressed, and the capacity retention rate after charge / discharge cycles can be increased and the resistance increase rate can be reduced.

[0084] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.

[0085] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.

[0086] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.

[0087] As the non-aqueous solvent, it is preferable to use at least one of a cyclic carbonate and a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When a cyclic carbonate and a chain carbonate are used in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0088] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0089] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0090] The content of the electrolyte salt in the non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 Less than 0.3 mol / dm is preferred. 3 More than 2.0mol / dm 3 Less than 0.5 mol / dm is more preferable. 3 More than 1.7mol / dm 3 More preferably, 0.7 mol / dm 3 More than 1.5mol / dm 3 The following is particularly preferable: By setting the content of the electrolyte salt within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.

[0091] The non-aqueous electrolyte may contain various additives as other components. Examples of the other components include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, Examples of the suitable cyclohexanedicarboxylic anhydride include ethylene sulfite, propylene sulfite, dimethyl sulfite, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, and tetrakistrimethylsilyl titanate. These may be used alone or in combination of two or more.

[0092] The content of the components (other components) other than the compound represented by the above formula 1, the nonaqueous solvent and the electrolyte salt contained in the nonaqueous electrolyte is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.1% by mass or more and 7% by mass or less, even more preferably 0.2% by mass or more and 5% by mass or less, and particularly preferably 0.3% by mass or more and 3% by mass or less, based on the total amount of the nonaqueous electrolyte. This content may be 1% by mass or less or 0.1% by mass or less. By setting the content of the other components within the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0093] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0094] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the form of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these materials, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of liquid retention of non-aqueous electrolyte. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferable from the viewpoint of shutdown function, and polyimide and aramid are preferable from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0095] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride and barium fluoride; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the nonaqueous electrolyte storage element.

[0096] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0097] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0098] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The nonaqueous electrolyte storage element is preferably produced by the following method: That is, a method for producing a nonaqueous electrolyte storage element according to one embodiment of the present invention includes preparing a positive electrode containing a positive electrode active material (positive electrode preparation step), and preparing a nonaqueous electrolyte containing the compound represented by the above formula 1 (nonaqueous electrolyte preparation step).

[0099] (Positive electrode preparation process) The positive electrode preparation step may be, for example, a step of preparing a positive electrode. The positive electrode can be prepared using a positive electrode mixture paste.

[0100] The positive electrode mixture paste usually contains a positive electrode active material and a binder, and further contains other components as necessary. The positive electrode mixture paste can be obtained by mixing these components. The positive electrode mixture paste is applied to the surface of the positive electrode substrate and dried to obtain a positive electrode.

[0101] The positive electrode mixture paste usually uses an organic solvent as a dispersion medium, such as polar solvents such as N-methyl-2-pyrrolidone (NMP), acetone, and ethanol, and non-polar solvents such as xylene, toluene, and cyclohexane.

[0102] The method for applying the positive electrode mixture paste is not particularly limited, and may be a known method such as roller coating, screen coating, or spin coating.

[0103] (Non-aqueous electrolyte preparation process) The non-aqueous electrolyte preparation step may be, for example, a step of preparing a non-aqueous electrolyte. The non-aqueous electrolyte can be prepared, for example, by mixing the compound represented by the above formula 1 with other components (electrolyte salt, non-aqueous solvent, etc.).

[0104] The manufacturing method may include other steps included in a manufacturing method of a normal nonaqueous electrolyte storage element in addition to the positive electrode preparation step and the nonaqueous electrolyte preparation step. The manufacturing method may include, for example, preparing a negative electrode, forming an electrode body in which the positive electrode and the negative electrode are alternately stacked by stacking or rolling them with a separator interposed therebetween, housing the positive electrode and the negative electrode (electrode body) in a container, and injecting a nonaqueous electrolyte into the container. Usually, the electrode body is housed in a container, and then the nonaqueous electrolyte is injected into the container, but this order may be reversed. After these steps, the injection port is sealed to obtain a nonaqueous electrolyte storage element.

[0105] <Other embodiments> The present invention is not limited to the above embodiment, and can be embodied in various modified and improved forms in addition to the above embodiment. For example, the positive electrode or negative electrode does not need to have an intermediate layer. In addition, the positive electrode of the nonaqueous electrolyte storage element does not need to have a clear layer formed by the positive electrode mixture. For example, the positive electrode may have a structure in which the positive electrode mixture is supported on a mesh-shaped positive electrode base material.

[0106] In the above embodiment, the nonaqueous electrolyte storage element is mainly a nonaqueous electrolyte secondary battery, but the nonaqueous electrolyte storage element may be another type of nonaqueous electrolyte storage element, such as a capacitor (electric double layer capacitor, lithium ion capacitor, etc.).

[0107] FIG. 1 is a schematic diagram of a rectangular nonaqueous electrolyte storage element 1, which is one embodiment of the nonaqueous electrolyte storage element according to the present invention. The figure is a see-through view of the inside of a container. In the nonaqueous electrolyte storage element 1 shown in FIG. 1, an electrode body 2 is housed in a container 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode mixture and a negative electrode having a negative electrode mixture with a separator interposed therebetween. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41, and the negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51. A nonaqueous electrolyte is poured into the container 3.

[0108] The shape of the nonaqueous electrolyte storage element (secondary battery) according to one embodiment of the present invention is not particularly limited, and examples thereof include a cylindrical battery, a square battery, a flat battery, a coin battery, and a button battery. The present invention can also be realized as an electricity storage device including a plurality of the nonaqueous electrolyte storage elements. One embodiment of the electricity storage device is shown in FIG. 2. In FIG. 2, an electricity storage device 30 includes a plurality of electricity storage units 20. Each of the electricity storage units 20 includes a plurality of nonaqueous electrolyte storage elements 1. The electricity storage device 30 can be mounted as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs). EXAMPLES

[0109] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0110] The additives (the compound represented by the above formula 1 and its substitutes) used in the examples and comparative examples are shown below. Compound (A): A compound represented by the following formula (A) (3,3'-dimethyl-2,2'-bithiophenyl) Compound (B): A compound (3-hexylthiophene) represented by the following formula (B): Compound (X): A compound represented by the following formula (X) (biphenyl)

[0111] [ka]

[0112] [Example 1] (Preparation of non-aqueous electrolyte) A non-aqueous solvent consisting of EC and EMC mixed in a volume ratio of 30:70 was used, and LiPF6 was added as an electrolyte salt at a concentration of 1.0 mol / dm 3 Additives of 0.3 mass % of VC, 1.0 mass % of lithium difluorophosphate, and 0.05 mass % of compound (A) were added to the solution to obtain a non-aqueous electrolyte.

[0113] (Preparation of positive electrode) LiNi as a positive electrode active material 0.5 Co 0.2 Mn 0.3 A positive electrode mixture paste was prepared containing O2, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of 93:4:3, and N-methyl-2-pyrrolidone (NMP) as a dispersion medium. This positive electrode mixture paste was applied to the surface of aluminum foil as a positive electrode substrate and dried to obtain a positive electrode. The positive electrode active material was in the form of secondary particles, with a primary particle diameter (average particle diameter) of 550 nm and a secondary particle diameter (average particle diameter) of 8 μm.

[0114] (Preparation of negative electrode) A negative electrode mixture paste was prepared containing graphite as the negative electrode active material, styrene butadiene rubber (SBR) as the binder, and carboxymethyl cellulose (CMC) as the thickener in a mass ratio of 98:1:1, with water as the dispersion medium. This negative electrode mixture paste was applied to the surface of copper foil as the negative electrode substrate, and dried to obtain a negative electrode.

[0115] (assembly) The above-mentioned positive electrode and negative electrode were wound with a polyolefin porous resin film separator interposed therebetween to prepare an electrode assembly. After inserting this electrode assembly into an aluminum rectangular container, the container lid was laser welded. After injecting the above-mentioned non-aqueous electrolyte into the container through an injecting hole provided in the container, the injecting hole was sealed to obtain a non-aqueous electrolyte storage element (non-aqueous electrolyte secondary battery).

[0116] [Examples 2 and 3, Comparative Examples 1 and 2] The nonaqueous electrolyte storage elements of Examples 2 and 3 and Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that a compound of the type and amount shown in Table 1 was added as an additive, or no additive was added.

[0117] [evaluation] (Initial performance evaluation) The following capacity confirmation test was carried out on each of the nonaqueous electrolyte storage elements of Examples 1 to 3 and Comparative Examples 1 and 2. The elements were charged at a constant current of 0.2 C to 4.25 V at 25° C., and then charged at a constant voltage of 4.25 V. The charge was terminated when the total charge time was 7.5 hours. After a 10-minute rest period was provided after the charge, the elements were discharged at a constant current of 1.0 C to 2.75 V at 25° C. The discharge capacity thus obtained was taken as the initial discharge capacity. In addition, the internal resistance (direct current resistance: DCR) at 25°C at 50% SOC was measured for each of the nonaqueous electrolyte storage elements of Examples 1 to 3 and Comparative Examples 1 and 2 by the following method. "SOC" (State of Charge) refers to the state of charge of the nonaqueous electrolyte storage element measured in a voltage range in which the nonaqueous electrolyte storage element is normally used, based on the rated capacity, and in this embodiment, refers to the state of charge measured under conditions in which the terminal voltage (closed circuit voltage (CCV)) is 4.25V (upper limit voltage) to 2.75V (lower limit voltage), based on the rated capacity. In this embodiment, the rated capacity was the initial discharge capacity. Each of the obtained nonaqueous electrolyte storage elements was charged at a constant current of 1.0C at 25°C to bring the SOC to 50%, and then discharged at a current of 0.2C at 25°C for 30 seconds. Thereafter, constant current charging was performed at a current of 0.2C for 30 seconds, followed by a rest period of 10 minutes. Next, the battery was discharged at a current of 0.5 C for 30 seconds, then charged at a constant current of 0.2 C for 75 seconds, and rested for 10 minutes. Finally, the battery was discharged at a current of 1.0 C for 30 seconds. The relationship between the current and the voltage 10 seconds after the start of discharge was plotted for each discharge current, and the internal resistance was calculated from the slope of the straight line obtained by plotting the three points.

[0118] In addition, for the positive electrodes of the nonaqueous electrolyte storage elements of Examples 1 to 3 and Comparative Examples 1 and 2, the potential was measured using the above method at 3.00 V vs. Li / Li + From the discharge state, the potential is 4.35V vs. Li / Li + The increase in the BET specific surface area was 57% in each case.

[0119] (Charge-discharge cycle test) The following charge-discharge cycle test was carried out on each of the nonaqueous electrolyte storage elements of Examples 1 to 3 and Comparative Examples 1 and 2. At 60°C, the elements were charged at a constant current of 1.0C up to 4.25V, and then charged at a constant voltage of 4.25V. The charge was terminated when the total charging time was 3 hours. A rest period of 10 minutes was then provided. Then, the elements were discharged at a constant current of 1.0C up to 2.75V, and then a rest period of 10 minutes was provided. In each of the Examples and Comparative Examples, this charge-discharge cycle was carried out 500 times.

[0120] (Performance evaluation after charge / discharge cycles) After the charge-discharge cycle test, a capacity confirmation test and measurement of internal resistance (DCR) at 25°C were performed in the same manner as in the above "Initial performance evaluation". The discharge capacity after the charge-discharge cycle test was divided by the initial discharge capacity to obtain the capacity retention rate (%). In addition, the increase in the internal resistance after the charge-discharge cycle test from the initial internal resistance was divided by the initial internal resistance to obtain the resistance increase rate (%). The respective measurement results are shown in Table 1.

[0121] [Table 1]

[0122] As shown in Table 1, the nonaqueous electrolyte storage elements of Examples 1 to 3, which include a nonaqueous electrolyte containing compound (A) or compound (B), which is a compound represented by the above formula 1, have a higher capacity retention rate after charge-discharge cycles than the nonaqueous electrolyte storage element of Comparative Example 1, which does not contain an additive in the nonaqueous electrolyte. In addition, the nonaqueous electrolyte storage elements of Examples 1 to 3 have a low resistance increase rate after charge-discharge cycles. In particular, Examples 1 and 2, which use compound (A), have these effects more excellent. Note that the nonaqueous electrolyte storage element of Comparative Example 2, which includes a nonaqueous electrolyte containing biphenyl, has a lower effect of improving the capacity retention rate and a higher resistance increase rate than the nonaqueous electrolyte storage element of Comparative Example 1, which does not contain an additive in the nonaqueous electrolyte. It is considered that the effect of improving the capacity retention rate after charge-discharge cycles and the effect of suppressing the resistance increase rate are unique effects that are sufficiently produced when a compound represented by the above formula 1 having a thiophene ring is used.

[0123] [Example 4] A nonaqueous electrolyte electricity storage element of Example 4 was obtained in the same manner as in Example 1, except that the positive electrode and negative electrode were prepared in the following manner. (Preparation of positive electrode) A positive electrode mixture paste was prepared containing LiFePO4 as a positive electrode active material, acetylene black as a conductive agent, and PVDF as a binder in a mass ratio of 90:5:5, and NMP as a dispersion medium. This positive electrode mixture paste was applied to the surface of an aluminum foil as a positive electrode substrate, and dried to obtain a positive electrode. (Preparation of negative electrode) A negative electrode mixture paste was prepared containing graphite as a negative electrode active material, acetylene black as a conductive agent, SBR as a binder, and CMC as a thickener in a mass ratio of 95.7:1.0:2.1:1.2, and using water as a dispersion medium. This negative electrode mixture paste was applied to the surface of copper foil as a negative electrode substrate, and dried to obtain a negative electrode.

[0124] [Example 5, Comparative Example 3] The nonaqueous electrolyte storage elements of Example 5 and Comparative Example 3 were obtained in the same manner as in Example 4, except that a compound of the type and content shown in Table 2 was added as an additive, or no additive was added.

[0125] [evaluation] (Initial performance evaluation) The following capacity confirmation test was carried out on each of the nonaqueous electrolyte storage elements of Examples 4 and 5 and Comparative Example 3. After charging at a constant current of 1.0 C to 3.6 V at 25° C., the elements were charged at a constant voltage of 3.6 V. The charging was terminated when the total charging time was 3 hours. After a rest period of 10 minutes was provided after charging, the elements were discharged at a constant current of 0.2 C to 2.0 V at 25° C. The initial discharge capacity was determined.

[0126] (Charge-discharge cycle test) The following charge-discharge cycle test was carried out on each of the nonaqueous electrolyte storage elements of Examples 4, 5 and Comparative Example 3. At 45°C, the elements were charged at a constant current of 1.0C up to 3.6V, and then charged at a constant voltage of 3.6V. The charge was terminated when the total charging time was 3 hours. A rest period of 10 minutes was then provided. Then, the elements were discharged at a constant current of 1.0C up to 2.0V, and then a rest period of 10 minutes was provided. In each of the Examples and Comparative Examples, this charge-discharge cycle was carried out 50 times.

[0127] (Performance evaluation after charge / discharge cycles) After the charge-discharge cycle test, a capacity confirmation test was performed in the same manner as in the "Initial performance evaluation" above. The discharge capacity after the charge-discharge cycle test was divided by the initial discharge capacity to obtain the capacity retention rate (%). The measurement results are shown in Table 2.

[0128] [Table 2]

[0129] As shown in Table 2, even when the positive electrode active material is LiFePO4, the capacity retention rate after charge-discharge cycles is increased by adding compound (A), which is a compound represented by the above formula 1, to the non-aqueous electrolyte. [Industrial Applicability]

[0130] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0131] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A positive electrode containing a positive electrode active material, and A non-aqueous electrolyte containing a compound represented by the following formula 1: Equipped with The positive electrode active material is a lithium transition metal composite oxide or a polyanion compound. 【Chemistry 1】 (In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 20 carbon atoms, a halogenated hydrocarbon group having from 1 to 20 carbon atoms, an alkoxy group having from 1 to 20 carbon atoms, or a halogenated alkoxy group having from 1 to 20 carbon atoms. n is an integer of from 2 to 4.

2. A positive electrode containing a positive electrode active material, and A non-aqueous electrolyte containing a compound represented by the following formula 2: Equipped with The positive electrode active material is a lithium transition metal composite oxide or a polyanion compound. 【Chemistry 2】 (In formula 2, R 1 and R 2 are hydrogen atoms. R 3a , R 3b , R 3c and R 3d are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 3 carbon atoms, a halogenated hydrocarbon group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, or a halogenated alkoxy group having 1 to 3 carbon atoms. m is an integer of 0 to 3. When m is 2 or more, multiple R 3c s and multiple R 3d s may be the same or different.)

3. A positive electrode containing a positive electrode active material, and A non-aqueous electrolyte containing a compound represented by the following formula 1: Equipped with The positive electrode active material is a secondary particle. 【Chemistry 3】 (In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a halogenated alkoxy group having 1 to 20 carbon atoms. n is an integer of 2 to 4.

4. A positive electrode containing a positive electrode active material, and A non-aqueous electrolyte containing a compound represented by the following formula 2: Equipped with The nonaqueous electrolyte electricity storage element, wherein the positive electrode active material is a polyanion compound. 【Chemistry 4】 (In formula 2, R 1 and R 2 are hydrogen atoms. R 3a , R 3b , R 3c and R 3d are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a halogenated alkoxy group having 1 to 20 carbon atoms. m is an integer of 0 to 3. When m is 2 or more, multiple R 3c s and multiple R 3d s may be the same or different.)

5. 4. The nonaqueous electrolyte storage element according to claim 1, wherein n is 2.

6. The above R 1 , R 2 and multiple R 3 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having from 1 to 3 carbon atoms, a halogenated hydrocarbon group having from 1 to 3 carbon atoms, an alkoxy group having from 1 to 3 carbon atoms, or a halogenated alkoxy group having from 1 to 3 carbon atoms.

7. The above R 1 and R 2 The nonaqueous electrolyte storage element according to claim 1 or 3, wherein each of the is a hydrogen atom.

8. The positive electrode active material contains a lithium transition metal composite oxide containing nickel, 4. The nonaqueous electrolyte storage element according to claim 1, wherein a content of nickel in the transition metals in the lithium transition metal composite oxide is 50 mol % or more.

9. 5. The nonaqueous electrolyte storage element according to claim 1, wherein the positive electrode active material is a secondary particle.

10. Providing a positive electrode containing a positive electrode active material; and Preparing a non-aqueous electrolyte containing a compound represented by the following formula 1: Equipped with The method for producing a non-aqueous electrolyte storage element, wherein the positive electrode active material is a lithium transition metal composite oxide or a polyanion compound. 【Chemistry 5】 (In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a halogenated alkoxy group having 1 to 20 carbon atoms. n is an integer of 2 to 4.

11. Providing a positive electrode containing a positive electrode active material; and Preparing a non-aqueous electrolyte containing a compound represented by the following formula 2: Equipped with The method for producing a non-aqueous electrolyte storage element, wherein the positive electrode active material is a lithium transition metal composite oxide or a polyanion compound. 【Chemistry 6】 (In formula 2, R 1 and R 2 are hydrogen atoms. R 3a , R 3b , R 3c and R 3d are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 3 carbon atoms, a halogenated hydrocarbon group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, or a halogenated alkoxy group having 1 to 3 carbon atoms. m is an integer of 0 to 3. When m is 2 or more, multiple R 3c s and multiple R 3d s may be the same or different.)

12. Providing a positive electrode containing a positive electrode active material; and Preparing a non-aqueous electrolyte containing a compound represented by the following formula 1: Equipped with The method for producing a nonaqueous electrolyte storage element, wherein the positive electrode active material is a secondary particle. 【Chemistry 7】 (In formula 1, R 1 , R 2 and multiple R 3 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a halogenated alkoxy group having 1 to 20 carbon atoms. n is an integer of 2 to 4.

13. Providing a positive electrode containing a positive electrode active material; and Preparing a non-aqueous electrolyte containing a compound represented by the following formula 2: Equipped with The method for producing a nonaqueous electrolyte storage element, wherein the positive electrode active material is a polyanion compound. 【Chemistry 8】 (In formula 2, R 1 and R 2 are hydrogen atoms. R 3a , R 3b , R 3c and R 3d are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a halogenated alkoxy group having 1 to 20 carbon atoms. m is an integer of 0 to 3. When m is 2 or more, multiple R 3c s and multiple R 3d s may be the same or different.)

Citation Information

Patent Citations

  • Secondary cell

    JP1986024174A

  • Lithium secondary battery

    JP2002025615A

  • Nonaqueous electrolytic secondary battery

    JP2013069659A

  • Nonaqueous electrolytic solution and lithium ion secondary battery

    JP2015072768A

  • Electrolyte, and secondary battery using the same

    JP2015149250A